Root-lesion nematode (Pratylenchus spp.) extraction from maize roots: a comparison of three methods - Thiruchchelvan, Nagarathnam; Casonato, Seona; Moukarzel, Romy; Condron, Leo; Kularathna, Manjula (New Zealand Plant Protection, 2024)
This study examines differences in extraction efficiency of three methods for extracting root-lesion nematodes (Pratylenchus spp.) from maize roots. The Baermann funnel, Whitehead & Hemming tray, and centrifugal-sugar flotation methods were evaluated for efficiency and clarity using microscopic observation. Statistical analysis confirmed significant differences among the methods. The centrifugal-sugar flotation method yielded the highest nematode count (1874±76 per 5 g of roots) but the clarity of the observation field under the microscope was lower due to root residues compared to the other two tested methods. The Baermann funnel method yielded 35.9% extraction efficiency (672±46 per 5 g of roots) compared to the centrifugal-sugar flotation method with higher clarity of the observation field than other tested methods. The Whitehead & Hemming tray presented a moderate level of observation field clarity compared to other tested methods with a nematode extraction efficiency of 60.8% (1140±53 per 5 g of roots) compared to the centrifugal-sugar flotation method. The results suggest that the Whitehead & Hemming tray could be a viable choice for nematode extraction, especially when both nematode numbers and microscopic clarity are important considerations. Understanding the restrictions of each methodology enhances the accuracy of nematode quantification leading to improved and updated data for maize producers in New Zealand.